Spacetime-varying couplings and Lorentz violation - Kostelecky, V. Alan (2018)
Spacetime-varying coupling constants can be associated with violations of local Lorentz invariance and CPT symmetry. An analytical supergravity cosmology with a time-varying fine-structure constant provides an explicit example. Estimates are made for some experimental constraints.